Working with girls and young women with autism spectrum condition : a practical guide for clinicians - Bullivant, Fiona Fisher (Jessica Kingsley Publishers, 2018)
This concise, practical guide shows how to enable girls and young women with ASD to reach their full potential, by adopting more individualised approaches. Drawing on clinical experience and clients' testimonies, it covers diagnosis, comorbidities, sensory issues, self-harm, emotional regulation, assessments, interventions and strategies